Managing the process of personnel development in the context of applying modern transformation technologies in the enterprise - Xiaofan, Hu (Харківський національний автомобільно-дорожній університет, 2024)
In this qualification work, the theoretical and methodological foundations of personnel development in the context of modern transformation technologies were examined. The economic activity of ME «Zmiiv-Service» was analyzed, identifying the enterprise's current structural configuration and its alignment with external environmental factors. A generalized matrix for identifying enterprise transformation directions was developed, aligning organizational management structures, coordination mechanisms, and key enterprise components. The definition of «personnel» was further developed, emphasizing its role as a core component of strategic potential and as both the authors and implementers of innovative changes at the enterprise. A comprehensive approach to enterprise transformation was proposed, ensuring timely and effective adjustments to the organizational structure. Additionally, methodological and practical recommendations for managing personnel development were improved, including the use of the «BOSCadrovyk» system and a functional model for management evaluation. Predictive assumptions – the proposed approaches and recommendations can be applied to enhance personnel development and enterprise management processes in other organizations, ensuring adaptability and competitiveness in the context of transformation and modernization.
Keywords: personnel development; transformation technologies; enterprise management; modernization; bos-cadrovyk system